MODERN NON-INVASIVE METHODS OF DIAGNOSTICS OF LIVER FIBROSIS IN CHILDREN - Arzibekov Abdikadir Gulyamovich (SAMARALI TA’LIM VA BARQAROR INNOVATSIYALAR JURNALI, 2025)
The review presents modern non-invasive methods for diagnosing liver fibrosis in children. Biochemical diagnostic tests for fibrosis are described, the structure of the liver parenchyma and the severity of fibrosis are assessed using traditional ultrasound techniques and non-invasive quantitative assessment of the liver structure: Acoustic Structure Quantification (ASQ) with determination of the density index. It is shown that ASQ allows obtaining valuable information about the acoustic structure of liver tissue in visual, parametric and numerical formats, which improves the quality, level and clinical significance of diagnostics.